2003
DOI: 10.1080/0963748031000084098
|View full text |Cite
|
Sign up to set email alerts
|

Nutrional aspect of zinc availability

Abstract: Zinc is an essential trace element in human nutrition and its deficiency is a world nutritional problem. However, the zinc content of foods is low and its availability is conditioned by several physiologic and dietary factors. For that reason, the objective of the present work is to compile past and present information about the influence of these factors on zinc availability to try to improve this availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 69 publications
4
28
0
1
Order By: Relevance
“…The association of the Zn with the yeast proteins and carbohydrate slowed the initial uptake rate within the first hour but also apparently reduced the excretion rate in the feces, but not the urine. Our findings with Zn yeast are consistent with previous studies that demonstrated animal proteins could improve Zn absorption [13]. Physiologically, this makes sense because the main dietary source of Zn is proteins [13].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The association of the Zn with the yeast proteins and carbohydrate slowed the initial uptake rate within the first hour but also apparently reduced the excretion rate in the feces, but not the urine. Our findings with Zn yeast are consistent with previous studies that demonstrated animal proteins could improve Zn absorption [13]. Physiologically, this makes sense because the main dietary source of Zn is proteins [13].…”
Section: Resultssupporting
confidence: 93%
“…Our findings with Zn yeast are consistent with previous studies that demonstrated animal proteins could improve Zn absorption [13]. Physiologically, this makes sense because the main dietary source of Zn is proteins [13].…”
Section: Resultssupporting
confidence: 93%
“…Both ZnY and ZnSO 4 were slowly eliminated in vivo with respective t 1/2, λz values of 7.68 and 7.93 h. During ZnY fermentation in the presence of Zn chloride or ZnSO 4 , a specific strain of yeast produced specific zinc compounds conjugated with proteins, peptides, and amino acids, which helped improve bioavailability of ZnY compared to inorganic Zn via enhanced intestinal absorption. Our findings with ZnY are consistent with previous studies in which animal proteins could improve Zn absorption [6, 10], which could physiologically illustrate protein as the major dietary source of Zn.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, zinc stabilizes the structures of proteins and nucleic acids and is also involved in immune phenomena (Salgueiro et al 2000;Camara and Amaro 2003).…”
Section: Resultsmentioning
confidence: 99%